SYNTHESIS AND CHARACTERIZATION OF TOLUENE SULFONIC ACID (TSA)-DOPED POLYPYRROLE NANOPARTICLES: EFFECTS OF DOPANT CONCENTRATIONS - S. Alva; R. S. Utami; L. K. Shyuan; I. Puspasari; A. B. Mohammad (Universitas Mercu Buana, 2016)
Nanoparticles of the conducting polymer polypyrrole in toluene sulfonic acid (PPy/TSA) were synthesized and characterized. The polymerization was process carried out in situ using ammonium persulfate (APS) as an oxidant. The particles were synthesized by varying the dopant concentration of para-toluene sulfonic acid over five sulphonic acid concentrations. The main objective of this study was to examine the effect of TSA dopant concentrations on the properties of polypyrrole nanoparticles. Understanding nature and characteristics of polypyrrole/TSA nanoparticles are important in determining whether the nanoparticles have the potential to be a component in the manufacture of fuel cells. The conducting polymer particles synthesized in this study were characterized using a particle analyzer, X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), spectroscopy UV-visible (UV-vis), thermogravimetric analysis (TGA) and electrical conductivity measurement. XRD shows that the particles generated possessed an amorphous structure, as also indicated by SEM images revealing the formation of aggregated and granular composite particles. Furthermore, the FTIR peak between 1273 and 1283cm-1 indicated that sulfonic acids (SO3-) groups were present in the structure of PPy. The size of the PPy/TSA nanoparticles was determined to be approximately 24-51 nm, and their conductivity measured to be 1.3 x 10-1 S/cm.